Refleksi Al-Qur'an Dalam Literasi Global (Studi Tafsir Maudhu’i Dalam Kajian Literasi) - Zamakhsyari Abdul Majid (Almarhalah | Jurnal Pendidikan Islam, 2019)
The construction of thinking from literacy becomes an understanding of what is believed to be the principle of the acquired knowledge, not just being able to read and write in a practical manner, but objectivity which is based on historical and philosophical. The routine of reading, writing and studying the content of the Qur'an forms a proportional and continuous structure of literacy objects through adjustments to global developments. Facing a changing situation that is accelerating, the community is experiencing continuous development. A knowledge will increasingly develop. In terms of social values 'and norms, old norms and values still exist, new values that will replace the old values that are considered irrelevant. Among the verses that contain literacy messages are Al-Alaq verses 1-5, Al-Qalam verse 1, Al-Kahfi 109, Al-Baqarah 78 79, Al-Ankabut 48-49, and Al-Baqarah 282. Al-Qur'an, there is three terms that indicate the meaning of reading, namely al-Qira'ah, tilawah and tartil, several verses of the Koran such as QS.Al-'Alaq first verse, QS.Al-Jumu'ah seconds verse, and QS.Al Muzammil the fourth verse are translated as 'reading'.